2012
DOI: 10.1055/s-0032-1309980
|View full text |Cite
|
Sign up to set email alerts
|

Gibt es Unterschiede in den gesundheitsschädlichen Wirkungen von Chrysotil- und Amphibol-Asbest?

Abstract: Zusammenfassung Ausgehend von der aktuellen Infragestellung gesundheitssch?dlicher Effekte des fr?her ganz vorrangig eingesetzten Chrysotil (Wei?-)-Asbests erfolgte eine Auswertung der Literatur ?ber In-vitro-, tierexperimentelle und epidemiologische Untersuchungen zur Wirkung der verschiedenen Asbestarten. Chrysotil verursacht nach epidemiologischen Untersuchungen seltener Pleurafibrosen und Pleuramesotheliome als andere Asbestarten. Ansonsten zeigt Chrysotil keine eindeutigen Abweichungen im inflammatorische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In a recent review of the literature, including in vitro and animal experiments and epidemiological studies, authors of this manuscript (XB, JS, HJW) concluded that ''As shown by epidemiological studies, chrysotile causes less pleural fibrosis and mesotheliomas when compared with other asbestos types. 10 [12][13][14][15] (with a cohort of 6 000 workers from four textile plants in North Carolina, USA). Employees were followed-up from 1950 to 2003 and the authors found a lung cancer standardized mortality ratio (SMR) 2.0 (95% CI 1.7-2.2), mesothelioma SMR 11.1 (95% CI 3.0-28.4); Relative risk (RR) increased with time since first employment and duration of employment and showed also an increased risk of asbestosis.…”
Section: Rationale and Discussionmentioning
confidence: 99%
“…In a recent review of the literature, including in vitro and animal experiments and epidemiological studies, authors of this manuscript (XB, JS, HJW) concluded that ''As shown by epidemiological studies, chrysotile causes less pleural fibrosis and mesotheliomas when compared with other asbestos types. 10 [12][13][14][15] (with a cohort of 6 000 workers from four textile plants in North Carolina, USA). Employees were followed-up from 1950 to 2003 and the authors found a lung cancer standardized mortality ratio (SMR) 2.0 (95% CI 1.7-2.2), mesothelioma SMR 11.1 (95% CI 3.0-28.4); Relative risk (RR) increased with time since first employment and duration of employment and showed also an increased risk of asbestosis.…”
Section: Rationale and Discussionmentioning
confidence: 99%